Lived experiences of healthcare workers on the front line during the COVID-19 pandemic: a qualitative interview study - Stephen Brett; Adam Lound; Kate Grailey (BMJ Open)
Objectives This study aimed to investigate the presence of perceived stressors, psychological safety and teamwork in healthcare professionals. As the timeframe for this study spanned the first wave of the COVID-19 pandemic, data were captured demonstrating the impact of the pandemic on these factors.Design Qualitative interview study.Setting All staff working within the emergency and critical care departments of one National Health Service Trust in London, UK.Participants Forty-nine participants were recruited using a purposive sampling technique and interviewed when the first wave of the COVID-19 pandemic had subsided.Main outcome measures Evaluation of changes in perceived stressors, psychological safety and teamwork in individuals working during the COVID-19 pandemic.Results The thematic analysis relating to a participant’s lived experiences while working during COVID-19 led to the construction of five key themes, including ‘psychological effects’ and ‘changes in team dynamics’. Several psychological effects were described, including the presence of psychological distress and insights into the aetiology of moral injury. There was marked heterogeneity in participants’ response to COVID-19, particularly with respect to changes in team dynamics and the perception of a psychologically safe environment. Descriptions of improved team cohesiveness and camaraderie contrasted with stories of new barriers, notably due to the high workload and the impact of personal protective equipment. Building on these themes, a map of key changes arising due to the pandemic was developed, highlighting potential opportunities to provide targeted support.Conclusions Working on the front line of a pandemic can have significant implications for healthcare workers, putting them at risk of psychological distress and moral injury, as well as affecting team dynamics. There is striking heterogeneity in the manifestation of these challenges. Team leaders can use the themes and qualitative data from this study to help identify areas for management focus and individual and team support.